Genetic insights into non-syndromic Tetralogy of Fallot - Althali, Nouf J.; Hentges, Kathryn E. (Frontiers in Physiology, 2022)
Congenital heart defects (CHD) include structural abnormalities of the heart or/and great vessels that are present at birth. CHD affects around 1% of all newborns worldwide. Tetralogy of Fallot (TOF) is the most prevalent cyanotic congenital cardiac abnormality, affecting 3 out of every 10,000 live infants with a prevalence rate of 5-10% of all congenital cardiac defects. The four hallmark characteristics of TOF are: right ventricular hypertrophy, pulmonary stenosis, ventricular septal defect, and overriding aorta. Approximately 20% of cases of TOF are associated with a known disease or chromosomal abnormality, with the remaining 80% of TOF cases being non-syndromic, with no known aetiology. Relatively few TOF patients have been studied, and little is known about critical causative genes for non-syndromic TOF. However, rare genetic variants have been identified as significant risk factors for CHD, and are likely to cause some cases of TOF. Therefore, this review aims to provide an update on well-characterized genes and the most recent variants identified for non-syndromic TOF.